Self-stabilized silicon-graphite composite negative electrode material with hierarchical pore structure and preparation method of self-stabilized silicon-graphite composite negative electrode material

By preparing silicon-graphite composite anode material with multi-stage pore structure, the structural rupture problem of silicon-based anode material due to volume expansion is solved, the circulation performance and stability of lithium-ion batteries are improved, and it is suitable for high-demand marine energy storage batteries.

CN120376625AActive Publication Date: 2025-07-25SANYA SCI & EDUCATION INNOVATION PARK WUHAN UNIV OF TECH

Patent Information

Application Number
CN202510837583.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-23
Publication Date
2025-07-25
Estimated Expiration
2045-06-23

AI Technical Summary

Technical Problem

The existing silicon-based anode material has structural rupture caused by volume expansion in lithium-ion batteries, repeated damage to the SEI film, and poor circulation performance, making it difficult to be suitable for high-demand marine energy storage batteries.

Method used

Micron-scale AlSi10Mg ternary alloy and graphite were mixed, and etched in oxalic acid solution after ball milling to prepare a silicon-graphite composite negative electrode material with multi-stage pore structure. The lithium storage capacity is enhanced through micropores, and the volume changes of mesoporous buffering are reduced to electrode powdering.

Benefits of technology

It achieves high capacity retention, excellent rate performance and cycle stability, and is suitable for large-scale industrial production, reducing irreversible capacity losses and extending battery life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120376625A_ABST
    Figure CN120376625A_ABST
Patent Text Reader

Abstract

The invention provides a hierarchical pore structure self-stabilized silicon-graphite composite negative electrode material and a preparation method thereof, and the preparation method comprises the following specific steps: S1, adding micron-sized AlSi10Mg ternary alloy particles and graphite into a solvent, carrying out ultrasonic dispersion, continuously stirring, and drying to obtain AlSi10Mg / graphite powder; s2, carrying out ball milling on the AlSi10Mg / graphite powder for later use; and S3, adding the ball-milled AlSi10Mg / graphite powder into an oxalic acid solution, and carrying out etching, washing and drying to obtain the target silicon-graphite composite negative electrode material named P-Si / Gr. The preparation process is simple, the synthesis is easy, the production efficiency is high, the preparation cost is low, the safety is high, and the prepared composite negative electrode material has high capacity retention ratio, excellent rate capability and cycling stability and good application prospect when being applied to a lithium battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium batteries, and particularly relates to a silicon-graphite composite anode material with a multi-porous structure and self-stability and a preparation method thereof. Background Art

[0002] At present, the lithium-ion battery industry is in a stage of double drive of technological iteration and market expansion. Due to its theoretical specific capacity as high as 4200 mAh / g (372 mAh / g for graphite anodes), silicon-based anode materials have become a key direction to break through the existing technical bottlenecks. In addition, silicon is the second most abundant element on the earth, easy to obtain, environmentally friendly, and has a relatively low electrochemical discharge potential. Therefore, silicon has the potential to replace graphite and revolutionize commercial lithium-ion battery anode materials, and also becomes a favorable choice for marine energy storage battery materials.

[0003] However, different from the intercalation reaction mechanism of graphite during lithiation, the lithiation process of silicon is essentially a process in which lithium ions undergo an alloying reaction with silicon materials during charge and discharge. During the charging of a lithium-ion battery, lithium ions in the positive electrode migrate to the silicon-based anode through the electrolyte. Silicon atoms form a lithium-silicon alloy through chemical combination with lithium, accompanied by a significant volume expansion (the expansion rate can reach more than 300%). This stage is called lithiation or lithium intercalation; during discharge, lithium ions are deintercalated from the lithium-silicon alloy and return to the positive electrode, and the silicon material structure shrinks and recovers. However, repeated volume changes will cause silicon particles to rupture, the electrode to pulverize, and trigger continuous destruction and regeneration of the solid electrolyte interface film (SEI film), resulting in irreversible loss of active lithium and capacity decay.

[0004] At present, the main means to solve the above problems are to alleviate the volume effect through the design of nano-silicon particles, carbon coating (such as silicon-carbon composite materials), porous structure regulation or prelithiation technology to improve the cycle stability. Or nano-sizing the silicon material and simultaneously compounding it with other materials (graphite, amorphous carbon, Sn, etc.) is a method to alleviate the problems of large volume expansion and poor conductivity of silicon anodes. However, silicon nano-materials have a low tap density, complex processes, high costs, and are difficult to manufacture on a large scale, restricting their development. At the same time, the preparation process of the current silicon-graphite composite anode material is complex, the discharge capacity is low, and the cycle performance is poor, affecting the life of lithium-ion batteries. The above technical problems reduce the adaptability of the silicon-graphite composite anode material to long-term charge and discharge in marine energy storage batteries, making it not well-suited for the application of large-scale marine energy storage batteries with high safety and reliability requirements, frequent charge and discharge, and high operation and maintenance costs. Summary of the Invention

[0005] In view of this, the present invention proposes a silicon-graphite composite anode material with a multi-porous structure and self-stability and a preparation method thereof.

[0006] The technical solution of the present invention is realized as follows: A preparation method of a silicon-graphite composite anode material with a multi-level pore structure and self-stability, the specific steps include: S1. Add micron-sized AlSi 10 Mg ternary alloy particles and graphite into a solvent, disperse them by ultrasonic wave, continue to stir, and dry to obtain AlSi 10 Mg / graphite powder; S2. Ball-mill the AlSi 10 Mg / graphite powder and set it aside; S3. Add the ball-milled AlSi 10 Mg / graphite powder into an oxalic acid solution for etching, washing, and drying to obtain the target silicon-graphite composite anode material, named P-Si / Gr.

[0007] Further, in step S1, the mass ratio of the micron-sized AlSi 10 Mg ternary alloy particles to graphite is 3-5:1; The solid-liquid ratio of the graphite to the solvent is 2-3:1 mg / mL; The solvent is at least one of water, methanol, ethanol, and N-methylpyrrolidone.

[0008] Further, the mass ratio of the micron-sized AlSi 10 Mg ternary alloy particles to graphite is 4:1.

[0009] Further, in step S1, the ultrasonic dispersion is carried out at 45-55 kHz and 20-25 °C for 20-60 min; the time for continuous stirring is 0.5-2 h.

[0010] Further, in step S2, the rotation speed of the ball-milling is 300-450 rpm, the time is 4-8 h, and the ball-to-material ratio is 5:1.

[0011] Further, in step S3, the solid-liquid ratio of the ball-milled AlSi 10 Mg / graphite powder to the oxalic acid solution is 10-12:1 mg / mL; the concentration of the oxalic acid solution is 0.5-1.5 mol / L.

[0012] Further, in step S3, the etching is carried out at 50-70 °C and 300-450 rpm for 12-48 h.

[0013] Further, the temperature of the etching is 60 °C, the rotation speed is 350 rpm, and the time is 24 h.

[0014] Further, in the silicon-graphite composite anode material in step S3, the particle size of the graphite is 5-7 μm, the thickness is 0.3-1 μm, the diameter of the silicon is 3-5 μm, and the pore diameter is 1.8-40 nm.

[0015] A silicon-graphite composite anode material with a self-stabilized hierarchical pore structure is obtained by the preparation method described in any one of the above.

[0016] Compared with the prior art, the beneficial effects of the present invention are as follows: 1. The hierarchical pore structure silicon-graphite composite anode material obtained by the preparation process of mixing, ball-milling, and oxalic acid etching dealloying of micron-sized AlSi 10 Mg alloy and graphite has a pore size range of 1.8 - 40 nm, covering the hierarchical pore structure of micropores and mesopores. The preparation process is simple, easy to synthesize, has high production efficiency, low preparation cost, high safety, and is suitable for large-scale industrial production; micron-sized AlSi 10 Mg ternary alloy particles have the characteristics of low cost and high tap density. The prepared P-Si / Gr material has excellent slurry coating performance, reduces the shedding of active substances, and can significantly improve its long-cycle performance; the present invention provides new ideas for the recycling and reuse of high-performance AlSi 10 Mg in the fields of aerospace, medical implants, construction engineering, and energy in the future.

[0017] 2. The hierarchical pore structure silicon-graphite composite anode material prepared by the present invention has a hierarchical pore structure of micropores and mesopores. The micropores enhance the lithium storage capacity, promote ion transport, and optimize conductivity. The mesopores buffer volume changes, reduce stress concentration during charge and discharge, avoid electrode pulverization and structural rupture. The two work together to improve the rate performance, cycle performance, and stability of the material. In addition, the porous network structure reduces the repeated rupture / regeneration of the SEI film through uniform volume expansion, reduces the loss of irreversible capacity, prolongs the cycle life, and the pore structure reduces the material density while maintaining a high capacity, which helps to improve the overall energy density of the battery.

[0018] 3. Compared with etching the AlSi 10 Mg alloy first and then mixing it with graphite, in the present invention, the micron-sized AlSi 10 Mg alloy and graphite are first mixed and then etched. This not only slows down the etching rate, ensures the integrity of the porous structure, but also improves the stability of the material. After cycling, the porous structure remains intact, can significantly improve the electronic conductivity of the material, and has better electrochemical performance.

[0019] 4. The composite anode material prepared by the present invention has a high capacity retention rate, excellent rate performance, and cycle stability when applied in lithium batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 SEM image of P-Si / Gr prepared in Example 1.

[0021] Figure 2 XRD pattern of P-Si / Gr prepared in Example 1.

[0022] Figure 3 Pore size distribution diagram of P-Si / Gr prepared in Example 1.

[0023] Figure 4 When P-Si / Gr prepared in Example 1 is used as the anode material of a lithium half-cell, at 200 mA•g -1 Charge and discharge curve diagram.

[0024] Figure 5 When P-Si / Gr prepared in Example 1 is used as the anode material of a lithium half-cell, at 200 mA•g -1 Cycling performance diagram.

[0025] Figure 6 When P-Si / Gr prepared in Example 1 is used as the anode material of a lithium iron phosphate full cell (LiFePO4), cycling performance diagram at 0.2C.

[0026] Figure 7 Rate performance diagram when P-Si / Gr prepared in Example 1 is used as the anode material of a lithium iron phosphate full cell (LiFePO4).

[0027] Figure 8 Front view, top view and right view of porous silicon of P-Si / Gr prepared in Example 1 after 50 cycles.

[0028] Figure 9 Slice in the Z-axis direction of the three-dimensional reconstructed structure diagram of porous silicon of P-Si / Gr prepared in Example 1 after 50 cycles.

[0029] Figure 10 SEM image of P-Si prepared in Comparative Example 1.

[0030] Figure 11 SEM image of P-Si-Gr prepared in Comparative Example 2.

[0031] Figure 12 When P-Si / Gr of Example 1, P-Si of Comparative Example 1, P-Si-Gr of Comparative Example 2, and Si of Comparative Example 3 are used as the anode materials of lithium half-cells, cycling performance diagram at 1000 mA•g -1 Cycling performance diagram.

[0032] Figure 13 Rate performance diagram when P-Si / Gr of Example 1, P-Si of Comparative Example 1, P-Si-Gr of Comparative Example 2, and Si of Comparative Example 3 are used as the anode materials of lithium half-cells. Detailed implementation mode

[0033] To better understand the technical content of the present invention, specific embodiments are provided below to further illustrate the present invention.

[0034] Unless otherwise specified, the experimental methods used in the embodiments of the present invention are all conventional methods.

[0035] The materials, reagents, etc. used in the embodiments of the present invention can be obtained from commercial channels unless otherwise specified.

[0036] Example 1 A preparation method of a silicon-graphite composite anode material with a self-stabilized hierarchical pore structure, the specific steps include: S1. Add 2 g of micron-sized AlSi 10 Mg ternary alloy particles and 500 mg of graphite into 200 mL of ethanol, ultrasonically disperse at 50 kHz and 25 °C for 30 min, continue to stir for 1 h, and dry at 80 °C for 24 h to obtain AlSi 10 Mg / graphite powder; S2. Ball-mill the AlSi 10 Mg / graphite powder, specifically: the ball-to-material ratio is 5:1, and ball-mill at 350 rpm for 6 h for standby; S3. According to the solid-liquid ratio of 10:1 mg / mL, add the ball-milled AlSi 10 Mg / graphite powder into 1 mol / L oxalic acid solution, etch at 60 °C and 350 rpm for 24 h, wash with deionized water 3 times, and dry at 80 °C for 24 h to obtain a silicon-graphite composite anode material, named P-Si / Gr.

[0037] A series of characterizations were carried out on the P-Si / Gr prepared in Example 1. At the same time, the battery performance of the P-Si / Gr prepared in Example 1 was detected and the cycling performance of P-Si / Gr was measured. The results are as follows.

[0038] Figure 1 From the SEM image, it can be seen that porous silicon adheres to the surface of graphite, and the porous structure is clear and complete.

[0039] Figure 2 From the XRD, it can be seen that the peaks of Mg and Al disappear due to etching, and the peak of graphite appears, indicating the successful synthesis of P-Si / Gr.

[0040] Figure 3 From the pore size distribution diagram, the presence of micropores with a diameter of ≤2 nm and mesopores with a diameter of 2 - 50 nm can be seen.

[0041] Figure 4 When P-Si / Gr is used as the anode material of a lithium half-cell, when the current density is 200 mA•g -1When the first Coulombic efficiency of the battery can be obtained from the charge-discharge curve as 82.3%, it has a high first Coulombic efficiency.

[0042] Figure 5 When P-Si / Gr is used as the negative electrode material of a lithium half-cell, when the current density is 200 mA•g -1 the initial discharge specific capacity is 2282 mAh•g -1 and the capacity retention rate after 100 cycles is 80.5%, showing a high capacity retention rate.

[0043] See Figure 12 In Example 1 of -1 when P-Si / Gr is used as the negative electrode material of a lithium half-cell, when the current density is 1000 mA•g -1 the initial discharge specific capacity is 2326 mAh•g

[0044] See Figure 13 In Example 1 of -1 when P-Si / Gr is used as the negative electrode material of a lithium half-cell, the specific capacity at a current density of 5 A•g -1 can reach over 1000 mAh•g -1 and when the current density is restored to 0.2 A•g

[0045] Figure 6 when P-Si / Gr is used as the negative electrode material of a lithium iron phosphate full cell (LiFePO4), the reversible specific capacity at 0.2C reaches over 150 mAh•g -1 and there is almost no capacity decay after 70 cycles, showing excellent cycle stability.

[0046] Figure 7 when P-Si / Gr is used as the negative electrode material of a lithium iron phosphate full cell (LiFePO4), it can be seen that it has good rate performance.

[0047] Figure 8 The HAADF three-dimensional reconstruction image of P-Si / Gr after 50 cycles of Figure 9 The three-dimensional reconstruction sectional view of P-Si / Gr after 50 cycles shows a clear pore structure and good pore structure retention, indicating that the P-Si / Gr material of the present invention has good stability and cycle performance.

[0048] Example 2 On the basis of Example 1, micron-sized AlSi10 The mass ratio of the Mg ternary alloy particles to the graphite was replaced with 3:1, i.e., 1.5 g of micron-sized AlSi 10 Mg ternary alloy particles and 500 mg of graphite, and the others were the same as in Example 1.

[0049] Example 3 On the basis of Example 1, the micron-sized AlSi 10 The mass ratio of the Mg ternary alloy particles to the graphite was replaced with 5:1, i.e., 2.5 g of micron-sized AlSi 10 Mg ternary alloy particles and 500 mg of graphite, and the others were the same as in Example 1.

[0050] Test Example The materials prepared in Examples 1 - 3 were subjected to a series of characterizations, and the test results are shown in Table 1.

[0051] Table 1

[0052] As can be seen from Table 1, when the mass ratio of AlSi 10 Mg to graphite was 3:1, the morphology of the prepared material was that most of the porous silicon was not composite. This was because the ability of AlSi 10 Mg to adhere to the graphite was weakened. When the mass ratio of AlSi 10 Mg to graphite was 5:1, the morphology of the prepared material was that there were residues of Al and Mg. This was because part of the graphite floated on the surface of the oxalic acid solution, resulting in that the AlSi 10 Mg adhering to it could not effectively react with the oxalic acid molecules and was incompletely etched. Therefore, the optimal mass ratio of AlSi 10 Mg to graphite in the present invention was 4:1.

[0053] Example 4 On the basis of Example 1, the etching time in step S3 was replaced with 12 h, and the others were the same as in Example 1.

[0054] Example 5 On the basis of Example 1, the etching time in step S3 was replaced with 48 h, and the others were the same as in Example 1.

[0055] Test Example The negative electrode materials prepared in Example 1, Example 4, and Example 5 were assembled in a lithium-ion half-cell for battery performance detection, and the results are shown in Table 2.

[0056] Table 2

[0057] As can be seen from Table 2, when the etching time is 12 h, the electrochemical performance decreases because Al and Mg are not completely removed. As the etching time increases, the electrochemical performance shows a trend of first increasing and then slowly decreasing. When the etching time is 24 h, the electrochemical data reach the best value. At this time, Al and Mg are completely removed, forming a composite structure of hierarchical porous silicon attached to graphite, and the electrochemical performance is fully released. Therefore, the optimal etching time of the present invention is 24 h.

[0058] Comparative Example 1 The difference from Example 1 is that: directly etch AlSi 10 Mg in oxalic acid to obtain a silicon-based material, named P-Si, and the others are the same as in Example 1.

[0059] That is, the material preparation method of this comparative example specifically includes the following steps: According to the solid-liquid ratio of 10:1 mg / mL, add 2 g of micron-sized AlSi 10 Mg ternary alloy particles into 1 mol / L oxalic acid solution, etch at 60 °C and 350 rpm for 24 h, wash with deionized water 3 times, and dry at 80 °C for 24 h to obtain a sample, named P-Si.

[0060] Comparative Example 2 The difference from Example 1 is that: first etch AlSi 10 Mg in oxalic acid to obtain a silicon-based material, and then ball-mill it with graphite to obtain a sample, named P-Si-Gr, and the others are the same as in Example 1.

[0061] That is, the material preparation method of this comparative example specifically includes the following steps: S1. According to the solid-liquid ratio of 10:1 m / mL, add 2 g of micron-sized AlSi 10 Mg ternary alloy particles into 1 mol / L oxalic acid solution, etch at 60 °C and 350 rpm for 24 h, wash with deionized water 3 times, and dry at 80 °C for 24 h to obtain a silicon-based material; S2. Ball-mill the silicon-based material and 500 mg of graphite powder. Specifically: the ball-to-material ratio is 5:1, and ball-mill at 350 rpm for 6 h to obtain a sample, named P-Si-Gr.

[0062] Comparative Example 3 Use micron-sized silicon with an average size of 1-3 μm, named Si.

[0063] See Figure 10 (SEM image of P-Si in Comparative Example 1), indicating that the pore channels of the P-Si material are broken.

[0064] Figure 11(SEM image of P-Si-Gr of Comparative Example 2). It can be seen that at the same scale, due to the energy destruction of ball milling, the porous structure shows a phenomenon of fragmentation and dispersion, and graphite and porous silicon are in physical contact without good combination.

[0065] Test Example The samples prepared in Example 1 and Comparative Examples 1-3 were assembled as the negative electrode material in a lithium-ion half-cell for electrochemical performance detection.

[0066] From Figure 12 cycling performance graph at 1000 mA•g -1 it can be seen that the specific capacity of P-Si / Gr in Example 1 of the present invention during the first discharge is 2326 mAh•g -1 , and it still maintains 69.2% of the capacity after 250 cycles. While the specific capacity of P-Si in Comparative Example 1 during the first discharge is 2726 mAh•g -1 , and it maintains 34.3% of the capacity after 250 cycles, indicating that the presence of graphite is beneficial to the stability of the sample. After adding graphite and performing the etching process, it has a positive impact on maintaining the material structure and can increase the cycling performance of the battery. The specific capacity of P-Si-Gr in Comparative Example 2 during the first discharge is 2145 mAh•g -1 , and it maintains 59.4% of the capacity after 100 cycles, indicating that compared with ball milling with graphite first and then etching in Example 1, the electrochemical performance and cycling performance of etching first and then ball milling with graphite in Comparative Example 2 decrease. The specific capacity of Si in Comparative Example 3 during the first discharge is 3183 mAh•g -1 , and it only maintains 7.4% of the capacity after 100 cycles, with poor cycling performance.

[0067] Figure 13 From the rate performance graph -1 it can be seen that P-Si / Gr in Example 1 of the present invention exhibits excellent rate performance, and the specific capacity can reach 1054 mAh•g -1 at a current density of 5 A•g -1 , and when the current density is restored to 0.2 A•g -1 , the specific capacity hardly decays. While the specific capacity of P-Si in Comparative Example 1 decreases to 411 mAh•g -1 at a current density of 5 A•g -1 , and when the current density is restored to 0.2 A•g -1 , the specific capacity decays significantly. The specific capacity of P-Si-Gr in Comparative Example 2 decreases to 715 mAh•g -1 at a current density of 5 A•g -1 , and when the current density is restored to 0.2 A•g -1The specific capacity at that time decreased. For the Si in Comparative Example 3, when the current density was 5 A•g -1 the specific capacity decreased to 55 mAh•g -1 When the current density was restored to 0.2 A•g -1 the specific capacity decreased significantly.

[0068] The above are only the preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent replacements, improvements, etc. made within the spirit and principles of the present invention shall be included within the protection scope of the present invention.

Claims

1. A preparation method of a silicon-graphite composite anode material with a self-stabilizing hierarchical pore structure, characterized in that, The specific steps include: S1. Add micron-sized AlSi 10 Mg ternary alloy particles and graphite into a solvent, disperse them by ultrasonic waves, continue stirring, and then dry them to obtain AlSi 10 Mg / graphite powder; S2. Grind the AlSi 10 Mg / graphite powder by ball milling for standby; S3. Add the ball-milled AlSi 10 Mg / graphite powder into the oxalic acid solution for etching, washing, and drying to obtain the target silicon-graphite composite anode material, named P-Si / Gr.

2. The preparation method of the hierarchically porous structure self-stabilized silicon-graphite composite anode material according to claim 1, wherein, In step S1, the mass ratio of the micron-sized AlSi 10 Mg ternary alloy particles to graphite is 3-5:1; The solid-liquid ratio of the graphite to the solvent is 2-3:1 mg / mL; the solvent is at least one of water, methanol, ethanol, and N-methylpyrrolidone.

3. The preparation method of the hierarchically porous structure self-stabilized silicon-graphite composite anode material according to claim 2, characterized in that, The mass ratio of the micron-sized AlSi 10 Mg ternary alloy particles to graphite is 4:

1.

4. The preparation method of the hierarchically porous structure self-stabilized silicon-graphite composite anode material according to claim 1, characterized in that, In step S1, the ultrasonic dispersion is carried out at 45-55 kHz and 20-25 °C for 20-60 min; the time for continuous stirring is 0.5-2 h.

5. The preparation method of the hierarchically porous structure self-stabilized silicon-graphite composite anode material according to claim 1, characterized in that, In step S2, the rotation speed of the ball milling is 300-450 rpm, the time is 4-8 h, and the ball-to-material ratio is 5:

1.

6. The preparation method of the hierarchically porous structure self-stabilized silicon-graphite composite anode material according to claim 1, wherein, In step S3, the solid-liquid ratio of the ball-milled AlSi 10 Mg / graphite powder to the oxalic acid solution is 10-12:1 mg / mL; the concentration of the oxalic acid solution is 0.5-1.5 mol / L.

7. The preparation method of the multi-porous structure self-stabilized silicon-graphite composite anode material according to claim 1, characterized in that, In step S3, the etching is carried out at 50-70 °C and 300-450 rpm for 12-48 h.

8. The preparation method of the hierarchically porous structure self-stabilized silicon-graphite composite anode material according to claim 7, wherein, The temperature of the etching is 60 °C, the rotation speed is 350 rpm, and the time is 24 h.

9. The preparation method of the multi-porous structure self-stabilized silicon-graphite composite negative electrode material according to claim 1, wherein, In step S3, in the silicon-graphite composite anode material, the particle size of the graphite is 5-7 μm, the thickness is 0.3-1 μm, the diameter of the silicon is 3-5 μm, and the pore diameter is 1.8-40 nm.

10. A silicon-graphite composite anode material with a self-stabilizing hierarchical pore structure, characterized in that Obtained by the preparation method according to any one of claims 1-9.

Citation Information

Patent Citations

  • Preparation method of graphene-based nanosilicon compound electrode material

    CN104009212A

  • Porous silicon material, and preparation method and application thereof

    CN105047892A

  • Silicon-carbon composite material, preparation method and application of silicon-carbon composite material

    CN105655555A

  • Method for synthesizing porous silicon-carbon composite material in one step by solid phase method and application of porous silicon-carbon composite material

    CN116190656A

  • Preparation of micron-scale silicon-carbon composite negative electrode material and application of micron-scale silicon-carbon composite negative electrode material in lithium ion battery

    CN117976861A

Cited By

  • Preparation method and application of carbon-coated silicon nanowire negative electrode material

    CN120809756A